2019
DOI: 10.1136/bmjopen-2018-024779
|View full text |Cite
|
Sign up to set email alerts
|

Does the ethnic density effect extend to obesity? A cross-sectional study of 415 166 adults in east London

Abstract: ObjectivesTo examine the prevalence of obesity by ethnic group and to examine the association between ethnic density and obesity prevalence.Design and settingCross-sectional study utilising electronic primary care records of 128 practices in a multiethnic population of east London.ParticipantsElectronic primary care records of 415 166 adults with a body mass index recorded in the previous 3 years.Outcome measures(1) Odds of obesity for different ethnic groups compared with white British. (2) Prevalence of obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Our findings of a relatively high prevalence of generalised obesity (females: 19%; males: 10%) and predisposition to OR-NCDS among UK Bangladeshis (females: 20% with increased risk, 42% having high or very high risk; males: 16% with increased risk, 12% with high or very high risk) conform to previous findings [3,41]. In comparison, the Health Survey for England (HSE) has reported that BMIbased obesity prevalence increased to 17% among Bangladeshi females and 6% among males in 2004 [42].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings of a relatively high prevalence of generalised obesity (females: 19%; males: 10%) and predisposition to OR-NCDS among UK Bangladeshis (females: 20% with increased risk, 42% having high or very high risk; males: 16% with increased risk, 12% with high or very high risk) conform to previous findings [3,41]. In comparison, the Health Survey for England (HSE) has reported that BMIbased obesity prevalence increased to 17% among Bangladeshi females and 6% among males in 2004 [42].…”
Section: Discussionsupporting
confidence: 90%
“…This is an important addition to the current literature on ethnic differences in obesity because central obesity is important for South Asian ethnic groups who have an increased risk of developing the metabolic syndrome (a group of risk factors for heart disease and other health problems such as diabetes) ( 2 , 3 ). The research is also novel because it presents the results at a national level for England, (using HSE and Census data) and because it includes a larger number of ethnic minority groups than other UK studies [e.g., ( 29 )]. These are the most up to date nationally representative data available; there have been no UK studies since that study central obesity (rather than BMI) and have a nationally representative sample of ethnic minorities.…”
Section: Discussionmentioning
confidence: 99%
“…This research is novel because there have been no studies in England that have explored the relationship between central obesity , and co-ethnic density/area-level deprivation for different ethnic groups. This research, therefore, builds on the previous body of knowledge on ethnic differences in obesity and, particularly, the BMI results from an East London cohort of five ethnic groups ( 29 ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The obesity epidemic, in particular, has disproportionately affected Black and Hispanic patients, with a higher prevalence of obesity in Black patients as compared with White patients, and with Black women having the highest odds of obesity of all racial and sex groups. 13 , 14 Black and Hispanic patients not only have a higher prevalence of obesity, but also an increased prevalence of cardiovascular disease—for which obesity is an independent, modifiable risk factor. 15 , 16…”
mentioning
confidence: 99%